Tengku Fakinah (D. 1933) Indonesia's Woman Ulama - Badrah Uyuni (MultiTech Publisher, 2023)
This study discusses the da'wah contribution of Indonesian female ulama Tengku Fakinah (d. 1933 AD). This research uses qualitative methods by making and observing works, books, academic research, videos, internet sources, and historical documents. The existing data is then analyzed using the explanatory analysis method where the logic of social phenomena is common sense by using historical, anthropological, and sociological approaches. This research tries to show the role model of female ulama Tengku Fakinah so that women today can learn and imitate the activities and struggles of these female ulama so that many benefits are generated for the improvement of the ummah, especially women. The concept of women scholars, contributions, strategies carried out by these women scholars are presented. Then the supporting and inhibiting factors of women ulama in preaching are also discussed so that they can be understood in depth.